The Role of Yoga in Patients Undergoing Radiotherapy: A Review of Current Literature - Giridharan, Selvaraj; Bhana, Rajanee; Ansari, Jawaher (International Research Journal of Ayurveda & Yoga, 2023)
The role of yoga in patients undergoing radiotherapy(RT) for cancer treatment has garnered increasing interest recently. RT can result in significant side effects, such as fatigue, sleep disturbance, and decreased physical function, and yoga has shown potential in alleviating these effects. This narrative review aims to provide an overview of the potential benefits of yoga as a supportive care strategy for patients undergoing anticancer RT. We discuss relevant randomised studies and evidence supporting the effectiveness of yoga interventions, focusing on their impact in stress reduction, mood improvement, symptom management and overall well-being. By incorporating yoga into the treatment plan, healthcare professionals can enhance the holistic care of cancer patients and potentially improve treatment outcomes.